Analisis Resepsi Mahasiswa Universitas Udayana Terhadap Lirik Lagu “Diri” Karya Tulus - Wangge, Katarina Miratriana Devi Gayatri; Suryawati, I Gusti Agung Alit; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2024)
Songs are a kind of mass communication where messages are sent one-way from performers to listeners. The song Diri by Tulus was released on March 3, 2022 and occupied the 3rd trending on March 9, 2022 in Youtube. The meaning of self-acceptance motivation, or liking yourself, is contained in the song Diri. This research find out the meaning of the message received by Udayana University students by the lyrics of the song Diri by Tulus. The analysis used is Reception Analysis with Stuart Hall's Encoding/Decoding Theory. Descriptive qualitative research methodology is employed. As a result, informants now occupy a more dominant position. Two informants were in the dominating position because they fully agreed with the meaning included in the preferred reading. The positions of the remaining three informants are mixed, namely dominat-position and oppositional-position because the majority agree and reject one meaning contained in the preferred reading. Keywords: Stuart Hall's Reception Analysis, "Diri" Song Lyrics by Tulus, Self-Acceptance Motivation, Encoding/Decoding Theory